First and Second Order Sensitivity Derivatives of Mechanical Systems Transfer Matrix - Wicher, J. (Engineering Transactions, 1987)
Sensitivity analysis in the frequency domain is considered in the paper. The first and second order sensitivity matrices of the mechanical lumped system are determined utilizing the transfer matrix partial derivatives. Examples presented in the paper show the effects of the parameter variation on amplitude frequency characteristics.